Strategic cousins : Australian and Canadian expeditionary forces and the British and American empires - Blaxland, John Charles, 1963- (McGill-Queen's University Press, 2006)
Australia and Canada may have different security strategies, reflecting contrasting domestic circumstances, but John Blaxland shows that common interests have led their forces to work together for over a century. Strategic Cousins examines the role of the professional armed forces of these geographically distant nations through a comparison of their historical experiences with expeditionary land forces.